PENGEMBANGAN E-MODUL DENGAN MENGGUNAKANAPLIKASI BOOK CREATOR PADA MATERI AKU DAN KEBUTUHANKU PESERTA DIDIK KELAS IV DI SDN KEBON PEDES 1 - Dwi Yangti Nurliana; Sandi Budiana; Elly Sukmanasa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Dwi Yangti Nurliana. 037120064. E-module development using a book creator on my material and my needs. This study uses a research and development approach at SDN Kebon Pedes 1 school. The research subjects of grade IV students of SDN Kebon Pedes 1 Bogor City consist of 28 students. The research was carried out in the even semester of the 2023/2024 school year. The method used in this study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. In this study, validation tests were carried out to experts. These experts are media experts, linguists, and material experts to develop and improve E-modules using book creators to teachers and students, and distribute student questionnaires to find out the feasibility of E-modules using book creators in learning. The results of the validation test by media experts with a percentage of 90% with very feasible criteria, linguists with a percentage of 100% with very feasible criteria, and material experts with a percentage of 84% with very feasible criteria. The results of the student response questionnaire showed a result with a percentage of 86% with a very feasible category, so the results show that the E-module is very feasible to be developed to students and is very feasible to be used as a teaching material in the learning process.